Body, Cosmos and Eternity : New Trends of Research on Iconography and Symbolism of Ancient Egyptian Coffins. - Sousa, Rogério (Archaeopress Egyptology Ser., 2014)
This volume collects papers from the symposium 'Body, Cosmos and Eternity: the Symbolism of Coffins in Ancient Egypt', convened at the historical building of the University of Port, February 2013.